2018
DOI: 10.1093/neuros/nyy466
|View full text |Cite
|
Sign up to set email alerts
|

Is the use of Stereotactic Electroencephalography Safe and Effective in Children? A Meta-Analysis of the use of Stereotactic Electroencephalography in Comparison to Subdural Grids for Invasive Epilepsy Monitoring in Pediatric Subjects

Abstract: BACKGROUND Stereoelectroencephalography (SEEG) is an alternative addition to subdural grids (SDG) in invasive extra-operative monitoring for medically refractory epilepsy. Few studies exist on the clinical efficacy and safety of these techniques in pediatric populations. OBJECTIVE To provide a comparative quantitative summary of surgical complications and postoperative seizure freedom associated with invasive extra-operative presurgical techniques in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…While the above findings stem from mixed-age studies, one meta-analysis of specifically pediatric patients found similarly favorable results 20. After SEEG, 2.9% of the pediatric patients suffered from ICH and no patients were reported to have infectious complications.…”
Section: Safetymentioning
confidence: 88%
“…While the above findings stem from mixed-age studies, one meta-analysis of specifically pediatric patients found similarly favorable results 20. After SEEG, 2.9% of the pediatric patients suffered from ICH and no patients were reported to have infectious complications.…”
Section: Safetymentioning
confidence: 88%
“…7,8) Its quick gain of popularity in a number of North American centers over a few years has contributed to the mounting recent evidence suggesting that SEEG is safer than SDE study. In contrast to the reported complication rates of SDE (5%-17%), [9][10][11][12][13] a meta-analysis on 4000 patients has shown that the rate is much lower (<1%) for SEEG. 14) A recent analysis of 239 patients that directly compared the two approaches has shown that implantation of SEEG electrodes is less time-consuming and less morbid, resulting in less postoperative pain and better seizure outcome in non-lesional cases.…”
Section: Introductionmentioning
confidence: 71%
“…In general, most centers prefer to use SDE in younger and SEEG in older children, with a cutoff around 3-to 4-year old. 12,19,20)…”
Section: Indications Of Seegmentioning
confidence: 99%
“…Yang et al [96] performed an institutional study comparing outcomes from SDG (n=52) and SEEG (n=48), observing higher rates of ICH and surgical site infection among SDG patients. In a meta-analysis comparing SDG and SEEG, Sacino et al [84] reviewed 23 papers featuring 974 children (SDG, 697; SEEG, 277), finding that SDG cases had a higher pooled-prevalence of CSF leak, infection, and ICH, as well as a lower overall seizure-freedom rate (SDG, 52.1% vs. SEEG, 66.5%).…”
Section: Safety Accuracy and Efficacymentioning
confidence: 99%